Short- and Long-Run Impacts of Rural Electrification: Evidence from the Historical Rollout of the U.S. Power Grid - Joshua Lewis; Edson R. Severnini (Institute of Labor Economics (IZA), 2017)
Electrification among American farm households increased from less than 10 percent to nearly 100 percent over a three decade span, 19301960. We exploit the historical rollout of the U.S. power grid to study the short- and long-run impacts of rural electrification on local economies. In the short run, rural electrification led to increases in agricultural employment, rural farm population, and rural property values, but there was little impact on the local non-agriculture economy. Benefits exceeded historical costs, even in rural areas with low population density. As for the long run, rural counties that gained early access to electricity experienced increased economic growth that persisted for decades after the country was fully electrified. In remote rural areas, local development was driven by a long-run expansion in the agricultural sector, while in rural counties near metropolitan areas, long-run population growth coincided with increases in housing costs and decreases in agricultural employment. This last result suggests that rural electrification stimulated suburban expansion.
Keywords: N72; N92; N32; O13; O18; Q48; 330; rural electrification; short run; long run; agriculture; suburbanization